Teaching Comparative Writing in an EFL Undergraduate Class through Interpreting Literature (IUBAT Review, 2026)
The mainstream English education system in Bangladesh has emphasised writing over the other three core language skills, as evidenced by the English tests in the secondary and higher secondary public examinations. Nevertheless, this pre-tertiary English education often fails to equip learners with the necessary proficiency in applying this skill practically, such as producing specific types of writing like descriptive, narrative, argumentative, and comparative. As a result of this learning gap, English undergraduates typically demonstrate low proficiency in context-specific academic writing. Furthermore, there is insufficient empirical evidence to address the issues and challenges of teaching comparative writing skills in classroom settings. Recognising this research gap in the Bangladeshi context, the current study planned a longitudinal process in natural classroom environments to explore issues related to teaching materials, classroom procedures, atmosphere, learning activities, and the duration of study for teaching comparative writing skills. The ‘CLASS’ (Classroom Assessment Scoring System) methodology was applied in this task-based classroom assessment procedure. Following the four guided lesson plans, students’ activities were collected, recorded, and compiled into a comprehensive report that revealed learners’ improvement in comparative writing, with significant progress by the fourth lesson. This study suggests that appropriate materials combined with guided learning processes help learners achieve targeted writing skills. It is worth noting that teachers serve as catalysts, guiding learners in selecting texts from their courses, providing structured lesson plans and activities, and evaluating learners’ progress.  IUBAT Review—A Multidisciplinary Academic Journal, 8(2): 306-328